Návrh a výroba interferenčních filtrů pro optická vlákna - Švábík, Marek (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Tato bakalářská práce je zaměřena na navržení a výrobu interferenčních filtrů nasaditelných na konce optických vláken. V práci je rozebírán výrobní postup od návrhu filtru, přes jeho výrobu nanesením tenkých vrstev na Si wafer. Následně je popsán design umožňující nasazení filtru na konec optického vlákna a způsob výroby takovéto nasaditelné čepičky. Samotná výroba probíhala leptáním waferu. Po nasazení byla funkčnost vyrobeného filtru testována měřením propustnosti.

This bachelor's thesis is focused on the design and fabrication of interference filters that can be mounted on the ends of optical fibers. The thesis discusses the production process from the filter design to its fabrication by depositing thin layers on a Si wafer. Subsequently, it describes a design that allows the filter to be mounted on the end of an optical fiber and the manufacturing method of such a mountable cap. The fabrication itself involved etching the wafer. After mounting, the functionality of the manufactured filter was tested by measuring its transmittance.
Design and fabrication of interference filters for optical fibers
Keywords: interferenční filtry; optická vlákna; čepička; Ramanova spektroskopie; interference filters; optical fibers; cup; Raman spectroscopy